HUBUNGAN POWER OTOT TUNGKAI DENGAN KECEPATAN LARI JARAK PENDEK SISWA PUTRA KELAS X MA MUHAMMADIYAH PEKANBARU - Ulfah Rizkiyah Mukhtar; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:The purpose of this study was to see the relationship between leg muscle strength and short distance running for class X students of MA Muhammadiyah Pekanbaru. The research site was carried out at MA Muhammadiyah Pekanbaru and the Riau University Mini Stadium field, Jln. Prof. Muchtar Luthfi, Pekanbaru. This research was conducted in November -December 2019. The sample in this study was a population of 14 male students of Class X MA Muhammadiyah Pekanbaru. This research is correlational by looking for relationships and proving the hypothesis of the relationship between two variables when the data are both variables and ratios. Based on the results of research that has been carried out by researchers and has gone through a detailed and statistical data processing process, it is based on the conclusion that there is a relationship between leg strength and short distance running speed for male students of class X MA Muhammadiyah Pekanbaru, because it is obtained rcount = 0, 92and rtabel. = α (0.05) = 0.553 where rcount> r table so that Ha can be accepted. There is a relationship between variable X and variable Y, where this relationship has a very strong relationship interpretation with the interpretation of the value r = 0.80-1.00 which can be seen from the results of the analysis of the correlation between leg muscle strength and the speed of running short distances.KeyWords:Leg Muscle Power Relationship, Short Distance Running Speed